2016
DOI: 10.1007/s10854-016-5118-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ba2+ doping on microstructure and electric properties of calcium copper titanate (CaCu3Ti4O12) ceramics

Abstract: The Ba 2? doped ceramics of Ca 1-x Ba x Cu 3 Ti 4 O 12 (x = 0.005, 0.01, 0.03, 0.05 and 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…have shown that J max varies from 0.1-32 mA/cm 2 [3, 42−48] . Meanwhile, Y and Mg co-doped samples of CaCu 3 Ti 4 O 12 have shown J max ≈ 28 mA/cm 2 [49] , Sr-Ni substituted CaCu 3 Ti 4 O 12 have exhibited J max ≈ 15 mA/cm 2 [14] , Pr-substituted CaCu 3 Ti 4 O 12 have demonstrated J max = 15 mA/cm 2 [50] , while Zn + Zr co-doped CaCu 3 Ti 4 O 12 thin films show J max in the range of 5-6 mA/cm 2 [51] . Finally, the composites, (1-x) (CaCu 3 Ti 4 O 12 )-(x)(0.1 Na 0.5 Bi 0.5 TiO 3 -0.9 BaTiO 3 ) with x = 0.02, 0.04, 0.06, 0.08 and 0.10, have shown J max ranging from 13-20 mA/cm 2 [52] .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…have shown that J max varies from 0.1-32 mA/cm 2 [3, 42−48] . Meanwhile, Y and Mg co-doped samples of CaCu 3 Ti 4 O 12 have shown J max ≈ 28 mA/cm 2 [49] , Sr-Ni substituted CaCu 3 Ti 4 O 12 have exhibited J max ≈ 15 mA/cm 2 [14] , Pr-substituted CaCu 3 Ti 4 O 12 have demonstrated J max = 15 mA/cm 2 [50] , while Zn + Zr co-doped CaCu 3 Ti 4 O 12 thin films show J max in the range of 5-6 mA/cm 2 [51] . Finally, the composites, (1-x) (CaCu 3 Ti 4 O 12 )-(x)(0.1 Na 0.5 Bi 0.5 TiO 3 -0.9 BaTiO 3 ) with x = 0.02, 0.04, 0.06, 0.08 and 0.10, have shown J max ranging from 13-20 mA/cm 2 [52] .…”
Section: Resultsmentioning
confidence: 98%
“…Cortes et al [13] performed dielectric and non-ohmic properties of Ca 2 Cu 2 Ti 4-x Sn x O 12 multiphasic ceramic composites. Comparative studies on pure and Sr 2+ and Ni 2+ doped and co-doped ceramics with special emphasis on the enhancement of dielectric properties have been published by Rhouma et al [14] . Wu et al [15] accomplished the effect of Ba 2+ substitution on microstructure and electrical properties of Ca 1-x Ba x Cu 3 Ti 4 O 12 ceramics.…”
Section: Introductionmentioning
confidence: 99%